ISPC Commentary on the Revised Proposal for CRP1.1 - September 2011 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2011)
ISPC Commentary on the revised proposal for CRP1.1 Dryland Systems: Integrated Agricultural Production Systems for the Poor and Vulnerable in Dry Areas.